Temporal trends of early mortality and its risk factors in HIV-infected adults initiating antiretroviral therapy in Uganda. (November 2020) - Ssempijja, Victor; Namulema, Edith; Ankunda, Racheal; Quinn, Thomas C.; Cobelens, Frank; Hoog, Anja van't; Reynolds, Steven J.
Abstract: Background: A decline in mortality rates during the first 12 months of antiretroviral therapy (ART) has been mainly linked to increased ART initiation at higher CD4 counts and at less advanced World Health Organization (WHO) clinical stages of HIV infection; however, the role of improved patient care has not been well studied. We estimated improvements in early mortality due to improved patient care. Methods: We conducted a retrospective cohort study of HIV-infected individuals ages 18 and older who initiated ART at the Mengo HIV Counseling and Home Care Clinic between 2006 and 2016. We conducted a mediation analysis using generalized structural equation models with inverse odds ratio weighting to estimate the natural direct and indirect effects of ART initiation time on early mortality. Findings: Among 6, 847 patients, most were female (69%), with a median age of 32 (interquartile range [IQR] = 28–38), versus a median age of 38 (IQR = 32–45) for males. The median CD4 count at ART initiation increased from 142 cells/ul (95% confidence interval [CI] = 135–150) in 2006–2010 to 302 cells/ul (95% CI = 283–323) in 2015–2016 ( p  < 0·001). The number of patients at WHO clinical stages I/II increased from 52% in 2006–2010 to 78% in 2015–2016 ( p  < 0·001). Annual early mortality decreased from 8·8 deaths/100 person years (PYS) in 2006 to 2.5 deaths/100 pys in 2016 ( p  < 0·001). Mediation by CD4 counts and WHO clinical stages accounted for 54% of the total effect of ART initiation timing on early mortality. In comparison, 46% remained as the direct effect, reflecting the contribution of improved patient care. Interpretation: Improved patient care practices should be promoted as a strategy for reducing early mortality after ART initiation, above and beyond the effects from ART initiation at higher CD4 counts and less advanced WHO clinical stage alone. Funding: This research was supported by the President's Emergency Plan for AIDS Relief (PEPFAR), the National Institute of Allergy and Infectious Diseases Division of Intramural Research, and the National Cancer Institute.